Student Perceptions on Interest in Tax Compliance: Understanding Tax Digitalization and Student Perceptions - Erawati, Teguh; Landing, Yoflantinus Wiranto (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to prove the influence of the Effect of Understanding Tax Digitalization and Student Perceptions on Interest in Tax Compliance (Case Study of Accounting Study Program Students at Sarjanawiyata Tamansiswa University).The approach used in this research is a qualitative approach. The study took a sample of Sarjanawiyata Tamansiswa University Accounting Students Class of 2020 and 2021 using the survey method data collection. The survey was conducted by distributing questionnaires using google forms containing questions to respondents, namely Accounting Students of Sarjanawiyata Tamansiswa University Class of 2020 and 2021. Primary data was obtained from the results of sampling Sarjanawiyata Tamansiswa University Accounting Students Class of 2020 and 2021 using survey method data collection. then processed using SPSS with descriptive analysis techniques. The results showed that there was Novelty: researchers added accounting knowledge to students' perceptions of interest in tax compliance whether accounting knowledge could make other factors such as, Interest in Tax Compliance, Tax Digitalization, Student Perceptions. Interest in Tax Compliance, Tax Digitalization and Student Perceptions have a positive or negative influence on company value.